Pricing Strategy Through the Lens of Islamic Principles - Kamal, Aqmari Zhafarina (Islamicate Institute, 2024)
This article examines pricing strategies through Islamic principles, focusing on fairness, justice, and consumer welfare. Unlike conventional pricing models that prioritize profit maximization, Islamic approaches embed ethical imperatives rooted in Qur’an, Hadith, and maqasid al-shariah. Using a qualitative normative method, the study analyzes literature, Islamic legal sources, and Indonesian case studies. Findings show that Sharia-compliant pricing must avoid riba, gharar, and zulm, while ensuring transparency and mutual benefit. Businesses can apply cost-based fairness, value-based ethical pricing, and competition-based non-predatory strategies. The research contributes theoretically by expanding marketing management literature with Islamic ethics and practically by offering guidance for businesses and regulators in Muslim markets. It concludes that Sharia-compliant pricing enhances trust, stabilizes markets, and strengthens the credibility of Islamic economic systems.